STRATEGI PENGEMBANGAN SISTEM PERTANIAN TERINTEGRASI (Studi Kasus : Kelompok Surya Tani di Desa Langkak, Kecamatan Kuala Pesisir Kabupaten Nagan Raya) - Rahmawati, Ulfa; Faizi, Rusdi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
An integrated agricultural system is a combined system of several agricultural sub-sectors that form a symbiotic-mutualism chain between one commodity and another that synergizes with each other. The development of an integrated agricultural system needs to be carried out for the independence of farmers who are economically, socially and environmentally sustainable. This study aims to analyze internal and external factors, formulate strategies and determine the best strategy that can be applied to the Surya Tani group in Langkak Village. This research was conducted in Langkak Village, Kuala Pesisir District, Nagan Raya Regency. The selection of farmer groups in this study was carried out purposively because they were farmer groups in the PPK ORMAWA BEM FP UTU village service program. This research was conducted from November to December 2022. The data analysis method used in this research is IFE, EFE, SWOT and QSPM analysis. The results of the analysis of internal factors and external factors show that the business is in a position to grow and develop.Results SWOT diagram, it is in quadrant I and  the SO Strategy is obtained. The strategy that must be carried out is an aggressive growth strategy, namely product development and market expansion by maximizing strengths and opportunities. The results of the QSPM analysis obtain strategic priority with a total TAS of 7.25.